Disaster Management using Internet of Things - Mrs. Saranjeet Kaur (International Journal of Advanced Science and Technology, 2020)
Natural disaster is a major challenge to the operation of a community or civilization that involvesserious life, properties, financial or environmental tragedy & Affects that overwhelm the willingnessof the person or civilization affected to use their own resources to cope with it.Experts are nowdocumenting incidents, disasters for even moreResearchers have been studying accidents for ourcentury now, & surveys of tragedy for nearly 40. There are a few mechanisms that form the ties in thechain when addressing crisis response, which operate in unison to fulfill the life cycle of emergencyresponse.This process will start with risk assessment, preparedness for disasters, emergencymanagement, resource distribution, reaction readiness and, lastly, recovery from disasters.Luckily,IoT has the answer to assist the organizations in the control of disasters at any level.